2022
DOI: 10.1177/1357633x211069664
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation models, barriers, and facilitators for cultural safety in telepsychiatry: A systematic scoping review

Abstract: Introduction: Indigenous peoples, and racial and ethnic minorities around the world experience significant mental health inequities. Telepsychiatry can contribute to addressing these inequities among these populations. However, it is first crucial to ensure the cultural safety of this tool as a critical step toward health equity. This review aimed to collate evidence regarding cultural adaptations, barriers, opportunities, and facilitators for telepsychiatry services supporting minority groups. Method: Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 80 publications
1
47
0
Order By: Relevance
“…In particular, the importance of incorporating their voices in identifying the necessary competencies required for delivering the service, setting up milestones and meaningful outcomes to be achieved by the service and developing standards and regulations to benchmark the service. These findings support Ruiz-Cosignani and colleagues’ 6 claim that it is indispensable for service providers to engage with communities when developing a service to ensure it is best suited to support the population it seeks to serve.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In particular, the importance of incorporating their voices in identifying the necessary competencies required for delivering the service, setting up milestones and meaningful outcomes to be achieved by the service and developing standards and regulations to benchmark the service. These findings support Ruiz-Cosignani and colleagues’ 6 claim that it is indispensable for service providers to engage with communities when developing a service to ensure it is best suited to support the population it seeks to serve.…”
Section: Discussionsupporting
confidence: 79%
“…The survey, developed on Qualtrics, was informed by the findings of a recent systematic scoping review of publications exploring culturally safe telepsychiatry. 6 This review helped the authors identified cultural adaptations, facilitators and barriers for the implementation of telepsychiatry services for Indigenous populations and ethnic minority groups. The survey was also informed by two stakeholder Hui (cultural gathering/meeting) in Auckland and Whangarei, New Zealand.…”
Section: Methodsmentioning
confidence: 99%
“…Ease of access to cultural liaisons, flexibility of sessions and wh anau (family) involvement during telepsychiatry sessions were also considered vital to ensure the best outcome for M aori both at a wh anau level and with the wider aspirations of M aori health outcomes. These principles pertaining to cultural safety are echoed in the recently published scoping review of telehealth services for indigenous populations and an international review on cultural safety (Moecke et al, 2023;Ruiz-Cosignani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Aotearoa’s Asian population is the fastest growing and second largest ethnic group; future planning of psychiatric services to serve them will also need to be considered (Soon Chow and Mulder, 2017; Statistics New Zealand, 2021). There is evidence that telepsychiatry could reduce inequalities in under-served populations (New Zealand Telehealth Resource Centre, 2021; RANZCP, 2021; Ruiz-Cosignani et al , 2022). Therefore, it is important for clinicians to provide culturally safe telepsychiatry services to optimise outcomes and not to further increase equity gaps for all ethnic groups in Aotearoa (Rahman et al , 2022; Ruiz-Cosignani et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation